Arthroscopic Transosseous Rotator Cuff Repair. Issue 7 (1st April 2023) - Stenson, James; Sanders, Brett; Lazarus, Mark; Austin, Luke
Abstract : Open transosseous rotator cuff repair (RCR) was the original benchmark surgical technique for RCR. The advent of arthroscopic and suture anchor technology shifted the paradigm from open to arthroscopic surgery. Although technological advances have progressed, they come at a cost. Suture anchor technology is expensive, optimal constructs have yet to be determined, and the technology may lead to challenging complications and revision scenarios. In more recent years, a return to transosseous bone tunnels has been described with new arthroscopic techniques, eliminating the need for suture anchors. The purpose of this article is to review the historical, biomechanical, clinical, and economic literature surrounding arthroscopic transosseous RCR.